Komitmen tanpa Konflik: Tawaran Teologi Pluralisme Kristiani - Samosir, Leonardus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2005)
Religions are always in tension between their claims of universality and the fact of their particularity. The potential of conflict arises precisely when the particular religion claims a universal truth. Christian theology of religious pluralism has managed to neutralize the tension by emphasizing the commitment to particular religion and at the same time the commitment to universal world problems. Such theological vision is supported by a philosophical reflection that sees truth as “revealed in“ but not “exclusively possessed“ by the particularity. In itself the truth remains transcendental, yet it shows its “traces“ in the positive outcomes of the particular.